Knowledge, attitude and readiness to use contraceptives among postpartum women at a tertiary hospital in Southwest Nigeria (2023)
Background: Postpartum family planning is vital in the prevention of unintended pregnancy and closely spaced pregnancies in the first year post-delivery. This study was designed to examine the postpartum women's knowledge, attitude, belief and readiness to contraceptive use. Methods: This descriptive cross-sectional study was conducted among one hundred and ninety-four consenting women, six weeks post-delivery, at the University College Hospital, Ibadan, Nigeria using an interviewer-assisted structured questionnaire. Data was analysed using IBM Statistics for Windows Version 23.0. Tests of association was done using chi-square and statistical significance was set at p-value of < 0.05. Results: Many of the respondents (60.8%) were in the age group 30-39 years and the majority (90.3%) had tertiary level of education. Most of the respondents got their information from health talks at antenatal clinic (42.8%) and health workers (42.3%).The majority (82.5%) of respondents were aware of contraception and 157(80.9%) intended to use contraceptives. The most preferred contraceptive methods were implants (19.1%). Respondents with three or more children alive(p=0.001), had statistically significant associations with prior use of contraception while those with the tertiary level of education(p=0.001), of the Christian religion (p=<0.001) and had contraceptive counselling during pregnancy (p=0.031)had statistically significant associations with good knowledge of contraception. Conclusion: The knowledge and readiness to use contraceptives was high but only about half were willing to adopt contraception post-delivery. There is therefore the need for the enactment of government policy and legislation that will ensure wide coverage and availability of contraception counselling among pregnant women.